LANDSLIDE ASSESSMENT ON UTP CUT SLOPE - ABDUL RASHID, NUR AMIRA (Universiti Teknologi PETRONAS, 2017)
This project aims to study the causes and design the slope failure at Block 14, Universiti Teknologi PETRONAS (UTP). The causes of the slope failure need to be investigated and it can prevent the slope failure occur again. Preliminary observation, site survey, soil investigation, soil laboratory testing and design the stability of cut slope are the methodology for this project. This project started with preliminary observation which performs the observation on the cut slope current condition, drainage system, type of vegetation and the surrounding of the cut slope. Site survey consists of topography survey as to identify the current geometry of the cut slope. In this project, there are two methods for soil investigation, which are open pit sampling and rotary wash boring. Water stand pipe and an inclinometer have been installed to monitor the ground water table and measure the movement of the cut slope respectively. Soil laboratory testing is used to determine the soil parameters of the cut slope and the list of tests are moisture content, atterberg limit, sieve and hydrometer analysis and triaxial test. GeoStudio software utilized to design the stability of cut slope by using slope/w application. The slope failure has caused by the poor maintenance at the drainage channels and modified slope has been designed using rock filling.